Description Of Maternal Characteristics And Causes Of Maternal Deaths In Serang District In 2022 - Fifi Musfirowati; Lukmanulhakim; Innama Sakinah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: Maternal mortality is still a problem globally and especially occurs in developing countries, including Indonesia. Objectives: Serang Regency has the highest number of maternal deaths in Banten Province. Maternal Mortality Rate (MMR) is a very important indicator of the level of public health. Maternal mortality is an indicator that describes the health status of women. This study aims to describe maternal characteristics and the causes of maternal death in Serang Regency. Methods: The type used in this research is analytical descriptive with a survey method and uses a cross sectional approach. The sample in this study was 52 using the Total Sampling technique. Results: The results of this study were that the majority of maternal deaths were caused by bleeding, 8 cases (15.4%), pre/eclampsia, 20 cases (38.5%), PROM, 1 case (1.9%), and others. as many as 23 cases (44.2%), then mostly aged <20 or >35 years as many as 15 cases (28.8%), and those aged 20-35 years as many as 37 cases (71.2%), parity <1 or >4 children as many as 25 cases (48.1%) and those with parity 2-3 as many as 27 cases (51.9%), ANC visits >6 times as many as 31 cases (59.6%), and <6 times as many as 21 cases (40.4%), non-health worker birth attendants as many as 11 cases (21.2%) and health workers as many as 41 cases (78.8%), place of delivery at home as many as 11 cases (21.2%), DOA 8 cases (15.4%), community health center 2 cases (3.8%), and hospital 31 cases (59.6%). Conclusions: Complete mortality data is needed to assess the causes of death. Appropriate assessment provides input for improving handling and policy making in the future